2023
DOI: 10.3389/fpsyg.2023.1068396
|View full text |Cite
|
Sign up to set email alerts
|

Uses of 360° video in referees' reflectivity training: Possibilities and limitations

Abstract: IntroductionA pedagogical innovation backed by an online device using 360° video had been devised to train young team sports referees (handball, soccer, rugby) to be more reflective. The objective of this exploratory research was to investigate the ways young student referees use 360° videos in allo-confrontation when carrying out some exercises involving open questions about their viewing experience.MethodsStudent referees' answers were recorded. A grounded analysis of these answers enabled us not only to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This case study represents a response to Kittel et al's (2022) recommendation for testing mobile 360°video uses in a sport officiating context (compared with fixed 360°video on a tripod at the side of the pitch). It also extends previous isolated decision-focused aims (Kittel et al, 2019) of 360°video in sport official training and builds on Boyer et al's (2023) recent investigation into mobile 360°video use for reflectivity skills by focusing on sport-specific, performance enhancement benefits.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…This case study represents a response to Kittel et al's (2022) recommendation for testing mobile 360°video uses in a sport officiating context (compared with fixed 360°video on a tripod at the side of the pitch). It also extends previous isolated decision-focused aims (Kittel et al, 2019) of 360°video in sport official training and builds on Boyer et al's (2023) recent investigation into mobile 360°video use for reflectivity skills by focusing on sport-specific, performance enhancement benefits.…”
Section: Discussionmentioning
confidence: 59%
“…Although there has been a surge in the use of point-of-view cameras (POV) in sport officiating training, which allows mobile capture of the referee's performance, it can often provide only a narrow scope of view. It has been suggested that mobile approaches to 360°video capture could provide moving images that give a more unique perspective and better immersion in performance (Boyer et al, 2023;Kittel et al, 2022). Head-or body-mounted mobile approaches to capturing 360°video (where one or more 360°video cameras are affixed on the referee using a chest or head harness) to be used for training and reflective practices have yet to be tested as a potential performance enhancement tool.…”
Section: Q5mentioning
confidence: 99%
See 3 more Smart Citations